Chinese patent medicine (Jinlong Capsule) for gastric cancer: Protocol for a systematic review and meta-analysis. Issue 23 (5th June 2020) - Li, Jianwei; Han, Bin; Sun, Guangzong; Zheng, Zhong; Mu, Ying; Chi, Jingxia
Abstract: Background: JLC has been widely applied as a promising adjunctive drug for GC. However, the exact effects and safety of JLC have yet to be systematically investigated. We aimed to summarize the efficacy and safety of JLC for the treatment of advanced GC through the meta-analysis, in order to provide scientific reference for the design of future clinical trials. Methods: The protocol followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. Relevant randomized controlled trials were searched from Cochrane Library, PubMed, Web of Science (WOS), Excerpt Medica Database (Embase), Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), China Scientific Journal Database (VIP), and Wanfang Database. Papers in English or Chinese published from their inception to January 2020 will be included without any restrictions. Study selection and data extraction will be performed independently by 2 investigators. The clinical outcomes including overall response rate, complete response rate, overall survival, Disease-free survival, quality of life (QoL), immune function, and adverse events, were systematically evaluated. Review Manager 5.3 and Stata 14.0 were used for data analysis, and the quality of the studies was also evaluated. Results and conclusion: The findings of this research will be published in a peer-reviewed journal, and provide more evidence-based guidance in clinical practice. International Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY) registration number: INPLASY202040105. URL: https://inplasy.com/inplasy-2020–4–0105/